Enablers and barriers to innovation activities in call centres - Smith, Marisa K.; Ball, Peter D.; van der Meer, Robert (Cranfield University, 2009)
Call centres have an operating model that aim to reduce costs - this has led to both customers and employees having issues with the current model. This has led to the view that contact centres are not entities in which innovation would occur. This paper identifies the barriers and enablers to innovation activities within call centres and discusses the implications of these to the wider service context.
Keywords: Innovation; services; call centres